2022
DOI: 10.2147/prbm.s363757
|View full text |Cite|
|
Sign up to set email alerts
|

The Motors of COVID-19 Vaccination Acceptance Scale (MoVac-COVID19S): Measurement Invariant Evidence for Its Nine-Item Version in Taiwan, Indonesia, and Malaysia

Abstract: Background: As the number of COVID-19 cases grows worldwide, one solution to the global pandemic is vaccination. Unfortunately, the hesitancy of receiving vaccines is still high, particularly among younger age groups (eg, students). Because the hesitancy of receiving vaccines is an important issue, instruments have been developed to assess vaccine hesitancy. Moreover, the use of these instruments among specific groups such as students is of critical importance. Aim: The present study examined the psychometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Nevertheless, this traditional multifactor model result is limited to determine such dimensionality, a limitation in the literature that required further testing, as discussed below. The 9-item version of the MoVac-COVID19S demonstrated a good fit, based on Asparouhov and Muthén (2018), which was superior to previous scale validations conducted in Taiwan, Indonesia, and Malaysia (Pramukti et al, 2022). This highlights the critical role of cultural appropriateness in psychometric assessments, advocated by the classical test theory, and reaffirms our version's validity in a German sample (Cooper, 2023;Yeh et al, 2021).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Nevertheless, this traditional multifactor model result is limited to determine such dimensionality, a limitation in the literature that required further testing, as discussed below. The 9-item version of the MoVac-COVID19S demonstrated a good fit, based on Asparouhov and Muthén (2018), which was superior to previous scale validations conducted in Taiwan, Indonesia, and Malaysia (Pramukti et al, 2022). This highlights the critical role of cultural appropriateness in psychometric assessments, advocated by the classical test theory, and reaffirms our version's validity in a German sample (Cooper, 2023;Yeh et al, 2021).…”
Section: Discussionsupporting
confidence: 68%
“…So far, Confirmatory Factor Analysis (CFA) results have indicated better fit indices and internal consistency for the 9-item version of the MoVac-COVID19S compared to the 12-item version of the MoVac-COVID19S among Chinese university students (Chen et al, 2021). Pramukti et al (2022) also found out that the one-factor structure of the MoVac-COVID19S fitted well among Indonesian and Malay university students compared to Taiwanese participants; however, the four-factor structure was fully supported among participants in each of these countries (see also Chen et al, 2022).…”
mentioning
confidence: 99%
“… 19 The MoVac-COVID19S item scores were unified in the same direction and summed (scores ranging between 12 and 84) with higher scores indicating greater motivation for COVID-19 vaccine uptake. 20 , 21 An example item is “ Vaccination is a very effective way to protect me against COVID-19. ” The MoVac-COVID19S has been validated across different populations, 22 including the Taiwanese population.…”
Section: Methodsmentioning
confidence: 99%
“…Multigroup CFA was used to examine measurement invariance of the GDT and GADIS-YA across gender (male vs. female) and across gaming time (< 2 hours vs. ≥ 2 hours). For each instrument and each variable for invariance testing, there were three nested models: (i) configural model that did not constrain any estimations equal across variable groups (e.g., male and female); (ii) metric equivalence model that constrained all factor loadings equal across variable groups; and (iii) scalar equivalence model that constrained all factor loadings and item threshold equal across variable groups (Chen et al, 2022b; Pramukti et al, 2022). Measurement invariance is supported when ΔCFI (i.e., CFI difference between every two nested models) > −0.01; ΔRMSEA (i.e., RMSEA difference between every two nested models) < 0.015; together with ΔSRMR (i.e., SRMR difference between every two nested models) < 0.03 (for factor loading) or < 0.01 (for item threshold) (Chen, 2007; Chen et al, 2022a).…”
Section: Methodsmentioning
confidence: 99%